A novel workflow for three-dimensional analysis of tumour cell migration. Issue 2 (14th February 2020) - Ketchen, Sophie; Rohwedder, Arndt; Knipp, Sabine; Esteves, Filomena; Struve, Nina; Peckham, Michelle; Ladbury, John E.; Curd, Alistair; Short, Susan C.; Brüning-Richardson, Anke
Abstract : The limitations of two-dimensional analysis in three-dimensional (3D) cellular imaging impair the accuracy of research findings in biological studies. Here, we report a novel 3D approach to acquisition, analysis and interpretation of tumour spheroid images. Our research interest in mesenchymal–amoeboid transition led to the development of a workflow incorporating the generation and analysis of 3D data with instant structured illumination microscopy and a new ImageJ plugin.